Integrated Estimation of a Cyber-Physical System’s Sustainability - Elena Schislyaeva; Elena Balashova; Inna Krasovskaya; Olga Saychenko; Elena Palkina (Energies, 2022)
Currently, in conditions of Industry 4.0, the use of cyber-physical systems in various fields is becoming widespread. This article is devoted to the problem of estimating CPS sustainability in the context of modern challenges faced by decision makers and IT developers in order to ensure effective proactive business process management using this innovative technology. The purpose of the research is to propose and substantiate a methodology for estimating CPS sustainability to ensure the reliability and strength of its elements, their interrelationships and interaction, as well as the effective functioning and development of this system in conditions of high dynamism and uncertainty of the external environment. In this study, we used methods of integral evaluation, synthesis, expert assessments, dynamic analysis, and systematic approach, and coined the term ‘CPS sustainability’. Our study showed that negative risks, external and internal threats may have a significant adverse impact on CPS sustainability. The reliability of this system should be evaluated on the basis of integrated indicators. The key indicators, reflecting the reliability of maintaining the properties of the CPS in a normal state of its function and further development, were identified. We propose a methodology for estimating CPS sustainability. In general, the presented results form the basis for improving CPS management to increase the effectiveness and efficiency of its functioning and development.